2021
DOI: 10.3390/pharmaceutics13081264
|View full text |Cite
|
Sign up to set email alerts
|

Increased In Vitro Intercellular Barrier Function of Lung Epithelial Cells Using Adipose-Derived Mesenchymal Stem/Stromal Cells

Abstract: With the emergence of coronavirus disease-2019, researchers have gained interest in the therapeutic efficacy of mesenchymal stem/stromal cells (MSCs) in acute respiratory distress syndrome; however, the mechanisms of the therapeutic effects of MSCs are unclear. We have previously reported that adipose-derived MSCs (AD-MSCs) strengthen the barrier function of the pulmonary vessels in scaffold-based bioengineered rat lungs. In this study, we evaluated whether AD-MSCs could enhance the intercellular barrier funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Indeed, previous work has suggested that AT2 cells are located near Pdgfra + mesenchymal cells, which promote AT2 self-renewal and differentiation into AT1 cells [ 24 ]. Moreover, paracrine signaling from mesenchymal populations can also provide therapeutic effects [ 21 , 25 ]. For instance, MSCs enhanced the barrier function in lung epithelial cells in a transwell culture model in which epithelial cells were grown in both direct and indirect contact conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous work has suggested that AT2 cells are located near Pdgfra + mesenchymal cells, which promote AT2 self-renewal and differentiation into AT1 cells [ 24 ]. Moreover, paracrine signaling from mesenchymal populations can also provide therapeutic effects [ 21 , 25 ]. For instance, MSCs enhanced the barrier function in lung epithelial cells in a transwell culture model in which epithelial cells were grown in both direct and indirect contact conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MSCs enhanced the barrier function in lung epithelial cells in a transwell culture model in which epithelial cells were grown in both direct and indirect contact conditions. Authors concluded that both direct adhesion and indirect paracrine effects strengthened the barrier function of lung alveolar epithelium in vitro [ 25 ]. Thus, it is likely that in this study, he initial support provided by BMC was can be attributed to potential direct cell to cell contact with AT2 cells as well as via paracrine signaling of neighbouring MSCs retained in the scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed a decrease in TEER in AECII at 4 h, followed by an increase at 6 h after YAP inhibition. The initial reduction in TEER indicates increased cell permeability due to AECII destruction (Metz et al 2020), and the subsequent increase in TEER could be due to the restoration of intercellular junctions among the cells resulting from AECII-to-AECI differentiation (Ishii et al 2021). The dynamic control of YAP appears to balance the degradation and reconstruction of alveolar epithelial integrity during AECII differentiation.…”
Section: Discussionmentioning
confidence: 99%